2022
DOI: 10.3390/genes13081494
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Machine Learning Methods for Multivariate Genomic Prediction Using the Sparse Kernels Method (SKM) Library

Abstract: Genomic selection (GS) changed the way plant breeders select genotypes. GS takes advantage of phenotypic and genotypic information to training a statistical machine learning model, which is used to predict phenotypic (or breeding) values of new lines for which only genotypic information is available. Therefore, many statistical machine learning methods have been proposed for this task. Multi-trait (MT) genomic prediction models take advantage of correlated traits to improve prediction accuracy. Therefore, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Japonica was studied by Monteverde et al [ 29 , 30 ]. The genotype data was obtained using Genotyping-by-Sequencing (GBS), and missing data was processed and filled using the FILLIN algorithm in TASSEL 5.0.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Japonica was studied by Monteverde et al [ 29 , 30 ]. The genotype data was obtained using Genotyping-by-Sequencing (GBS), and missing data was processed and filled using the FILLIN algorithm in TASSEL 5.0.…”
Section: Methodsmentioning
confidence: 99%
“…Pandey and his team used the Affymetrix GeneTitan platform to extract the genomic information of 318 lines of Groundnut and perform SNP genotyping [ 29 , 31 ]. After quality control, each genotype contained 8268 SNP markers, which were coded as 0, 1, and 2.…”
Section: Methodsmentioning
confidence: 99%
“…We compared the performance of the three models to discern the most effective algorithm for our predictive task [31]. This process guided us toward selecting the best model for predicting abnormal respiratory patterns in older adults.…”
Section: Comparisonmentioning
confidence: 99%
“…Genomic selection (GS) is frequently used for genetic improvement and has many advantages over phenotype-based selection [ 1 ]. Nevertheless, breeders face an adversity of challenges to improve the accuracy of the GS methodology, similar to multi-trait (MT) genomic prediction models, which take advantage of correlated traits to improve prediction accuracy [ 2 ] under multiple environments. Consequently, to accurately predict breeding values or phenotypic values is a challenge of primordial interest in GS, as the goal is to increase genetic gain.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, empirical evidence has shown that MT models are more efficient than single-trait (ST) models [ 13 ]. Some reasons why MT models are chosen over ST models [ 14 ] are that: (1) they capture complex relationships between correlated traits in a more efficient way, (2) they take advantage of the degree of correlation between lines and traits, (3) MT models offer better interpretability than ST models, (4) they are computationally more parsimonious to train than ST models, (5) more precise estimates of random effects of lines and genetic correlations between traits are obtained, which allows for improvement of the index selection, (6) they become more efficient for indirect selection as the precision of genetic correlation parameter estimates increases, and (7) they improve hypothesis testing because they reduce type I and II errors [ 2 ] due to a more precise estimates of parameters.…”
Section: Introductionmentioning
confidence: 99%